SME competitiveness and internationalization - internationalization of B5 - in-depth analysis of country United Kingdom plus international entry mode selection (export Vs. FDI modes) LR - Rebelo, Maria Luísa Meneres De Faria (2021)
This work project aims to build an internationalization strategy for B5, a tourism firm with multiple services and brands. The strategy for selecting international markets was performed using analytical approaches based on secondary data. The chosen target market was France, with Paris being the city chosen for a wholly-owned subsidiary. Finally, a marketing strategy and financial forecast were used to establish the expansion strategy. According to the financial forecast, the business is predicted to continue growing after 2025. Also, a literature review on international entry mode selection, export vs. FDI modes, was carried out, and an in-depth analysis of the United Kingdom.